2020
DOI: 10.1055/s-0040-1702175
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Analysis of Early and Late Readmissions following Free Tissue Transfer for Breast Reconstruction

Abstract: Background Traditionally, surgical quality outcomes are assessed using a 30-day postoperative window. For breast cancer patients undergoing free tissue transfer for breast reconstruction, we sought to describe the distribution of and specific risk factors for early and late readmissions within a 0- to 90-day postoperative period. Patients and Methods The Nationwide Readmissions Database was used to conduct a retrospective cohort study. Breast cancer patients undergoing free tissue transfer for breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…Variables independently associated with complications in this study included also a history of asthma or chronic obstructive pulmonary disease. This is in line with earlier studies [16,18] with free flaps and mastectomy combined with implant or muscular flap reconstruction [17]. In those studies, a significant correlation was found between COPD/ asthma and the need for revision surgery.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Variables independently associated with complications in this study included also a history of asthma or chronic obstructive pulmonary disease. This is in line with earlier studies [16,18] with free flaps and mastectomy combined with implant or muscular flap reconstruction [17]. In those studies, a significant correlation was found between COPD/ asthma and the need for revision surgery.…”
Section: Discussionsupporting
confidence: 91%
“…There are many studies evaluating postoperative complications and comorbidities associated with breast reconstructions [11][12][13][14][15][16][17][18], but only few have assessed the predictive risk factors for postoperative complications. It is common that only one or two surgical techniques are compared to or the follow-up time is 30 days postoperatively [14,19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Second, Magno-Padron et al recently described the classic 30-day complication variable as potentially missing a significant number of late readmissions and complications using the Nationwide Readmission Database. 32 This can also contribute to underestimation of the complication rate identified in our study. Moreover, we were not able to differentiate between flap types, which is also suggested to have different complication profiles.…”
Section: Discussionmentioning
confidence: 78%
“…The authors found a 4.3% wound-related readmission rate and identified several risk factors, such as hypertension, smoking, and obesity, that were associated with a higher risk of readmission. 29 In the present paper, we were able to match for these known risk factors, obliterating their impact on outcomes, and improving the strength of the analysis.…”
Section: Discussionmentioning
confidence: 89%